2022
DOI: 10.1126/sciadv.abn7901
|View full text |Cite
|
Sign up to set email alerts
|

CPK28-NLP7 module integrates cold-induced Ca 2+ signal and transcriptional reprogramming in Arabidopsis

Abstract: Exposure to cold triggers a spike in cytosolic calcium (Ca 2+ ) that often leads to transcriptional reprogramming in plants. However, how this Ca 2+ signal is perceived and relayed to the downstream cold signaling pathway remains unknown. Here, we show that the CALCIUM-DEPENDENT PROTEIN KINASE 28 (CPK28) initiates a phosphorylation cascade to specify transcriptional reprogramming downstream of cold-induced Ca 2+ signal. Plasma membrane (PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 71 publications
0
19
0
1
Order By: Relevance
“…These previous observations provide support for our finding based on protein-protein interaction studies, which indicate direct interactions between CPK6 and CPK28 with P2K1 (Figure 3). CPKs impart various effects on plant growth, development, and responses to abiotic and biotic stresses, primarily through the phosphorylation of their target proteins (Atif et al, 2019;Ding et al, 2022;Huang et al, 2020;Monaghan et al, 2015;Wei et al, 2014;Zhao et al, 2021). While the first study characterizing CPK28 in Arabidopsis revealed its involvement in plant stem elongation and vascular development (Matschi et al, 2013), it has been shown its crucial role in immune signaling (Monaghan et al, 2014) and abiotic stress responses (Ding et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These previous observations provide support for our finding based on protein-protein interaction studies, which indicate direct interactions between CPK6 and CPK28 with P2K1 (Figure 3). CPKs impart various effects on plant growth, development, and responses to abiotic and biotic stresses, primarily through the phosphorylation of their target proteins (Atif et al, 2019;Ding et al, 2022;Huang et al, 2020;Monaghan et al, 2015;Wei et al, 2014;Zhao et al, 2021). While the first study characterizing CPK28 in Arabidopsis revealed its involvement in plant stem elongation and vascular development (Matschi et al, 2013), it has been shown its crucial role in immune signaling (Monaghan et al, 2014) and abiotic stress responses (Ding et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A novel function of OsNLP3/4 in panicle development NIN-LIKE PROTEINs are pivotal transcription factors for early N signaling, N fixation and cold stress responses and act as receptors of nitrate, as recently reported for AtNLP7 (Mu & Luo, 2019;Jiang et al, 2021;Ding et al, 2022;Liu et al, 2022). However, the regulation of NLPs in development has rarely been studied.…”
Section: Discussionmentioning
confidence: 99%
“…RECEPTOR KINASE 4 (HERK4), WALL-ASSOCIATED KINASE 1 (WAK1), WAK2, and L-TYPE LECTIN RECEPTOR KINASE IV.1 (LECRK-IV.1) (Table S2). CPK28 is a multifunctional protein with roles in immune signaling (Monaghan et al, 2014(Monaghan et al, , 2015, vegetative-to-reproductive stage transition (Matschi et al, 2013(Matschi et al, , 2015, temperature stress responses (Hu et al, 2021;Ding et al, 2022b), and more (Jin et al, 2017;Ding et al, 2022a). The potential for CPK28 to associate with so many RKs and RLCKs at the plasma membrane may reflect this broad functionality.…”
Section: Identification Of Cpk28-associated Proteinsmentioning
confidence: 99%